Quick-curing anti-aging silicone sealant for photovoltaic module and preparation method of quick-curing anti-aging silicone sealant

By combining α,ω-dihydroxypolydimethylsiloxane and modified silicon micropowder, the additive sequence and reaction time are optimized, and the hydrophobic gas-phase white carbon black is introduced, which solves the problems of slow curing speed and poor construction performance of sealants for photovoltaic modules, and achieves the improvement of rapid curing and anti-aging performance.

CN119799268AActive Publication Date: 2025-04-11HUBEI XINGRUI SILICON MATERIAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411821018.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-11
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The sealant for existing photovoltaic modules is slow to cure, has poor construction performance, and is prone to overflow during assembly, which cannot meet the needs of efficient assembly and anti-aging.

Method used

By combining α,ω-dihydroxypolydimethylsiloxane and modified silicon micropowder, the additive order and reaction time of the additive are adjusted, hydrophobic vapor phase white carbon black is introduced, and modified silicon micropowder is used to replace nano calcium carbonate to optimize the curing rate and construction performance of the sealant.

Benefits of technology

It realizes rapid curing of sealant, reduces the probability of overflow, improves assembly efficiency and anti-aging performance, and ensures the reliability and service life of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799268A_ABST
    Figure CN119799268A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sealant materials, and particularly discloses a quick-curing anti-aging silicone sealant for a photovoltaic module and a preparation method of the quick-curing anti-aging silicone sealant. The invention relates to a quick-curing anti-aging silicone sealant for a photovoltaic module, which is prepared from the following raw materials in parts by weight: 450 parts of alpha, omega-dihydroxy polydimethylsiloxane 360 # imgabs 0 #, 425 parts of nano active calcium carbonate 275 # imgabs 1 #, 280 parts of modified silica powder 130 # imgabs 2 #, 10 parts of hydrophobic fumed silica 5 # imgabs 3 #, 40 parts of a cross-linking agent 30 # imgabs 4 #, 10 parts of a coupling agent 5 # imgabs 5 # and 0.4 part of dibutyltin dilaurate 0.1 # imgabs 6 #. According to the quick-curing anti-aging silicone sealant for the photovoltaic module, 20,000 mpa.s and 500,000 mpa.s of alpha, omega-dihydroxy polydimethylsiloxane are compounded, the hydrophobic fumed silica and the modified silica powder are introduced, and the types, the adding sequence and the reaction time of the auxiliaries are adjusted, so that the construction performance, the curing rate and the anti-aging performance of the sealant are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sealant materials, and in particular to a fast-curing anti-aging silicone sealant for photovoltaic modules. Background Art

[0002] Sealant for photovoltaic modules is a polymer material with high elasticity, high adhesion and low expansion. It can combine with moisture in the air at room temperature to cause cross-linking, and vulcanize into a high-performance elastomer. It has excellent bonding and sealing properties for metal and non-metal materials. It is mainly used for sealing and bonding between solar panels and back panels, between solar panels and glass, and between frames and solar panels. At present, the frame glue used in the photovoltaic industry is still mainly single-component deoxime silicone sealant. Its curing is a change in physical properties after contact with moisture. The product cures slowly, which greatly reduces the assembly efficiency of the production line and is prone to secondary glue overflow. In the assembly process, sealants with suitable extrusion properties have better construction performance, and excellent anti-aging properties ensure that the components can be used in various harsh environments. Therefore, it is of high economic value and practicality to develop a fast-curing and easy-to-construct fast-curing anti-aging silicone sealant for photovoltaic modules.

[0003] The Chinese invention patent application publication CN108048030A discloses a method for preparing a solar photovoltaic module sealant, comprising the following raw materials in parts by weight: 70-80 parts of polyorganosiloxane, 20-30 parts of filler, 5-15 parts of catalyst, 5-15 parts of tackifier, 3-9 parts of plasticizer, 2-6 parts of flame retardant, and 1-6 parts of crosslinking agent, wherein the polyorganosiloxane is a hydroxy-terminated polydimethylsiloxane, and the viscosity of the polyorganosiloxane at room temperature is 10,000-100,000 mPa.s, the filler is a mixture of light calcium carbonate, heavy calcium carbonate, nano calcium carbonate, and fumed silica, the tackifier includes isocyanate-modified alkyd resin and castor oil, the flame retardant is aluminum hydroxide and magnesium hydroxide, and the aluminum hydroxide and magnesium hydroxide are aluminum hydroxide and magnesium hydroxide modified by fatty acid, silane coupling agent or resin acid. The present invention adds tackifier and plasticizer to the base material, so that the produced sealant has good bonding performance and stability.

[0004] China invention patent application publication CN103232832A discloses a fast-curing sealant for solar photovoltaic modules, the raw materials of which include 100 parts of α,ω-dihydroxy polydimethylsiloxane, 60-80 parts of nano-activated calcium carbonate, 5-10 parts of fumed silica, 1-5 parts of anti-yellowing additive, 1-5 parts of coupling agent, 10-20 parts of cross-linking agent, 0.1-2 parts of catalyst A, 0.001-0.1 parts of catalyst B, and 1-10 parts of silicone oil plasticizer. The catalyst A is an organic tin chelate, and the catalyst B is dioctyltin dilaurate. The sealant of the invention can be cured quickly, resists yellowing, has good aging resistance, and has a wide range of adhesion to substrates.

[0005] Comparative analysis of the above patents shows that none of them optimizes extrusion, curing depth and aging at the same time. In order to meet the market demand, the inventor studies an anti-aging photovoltaic adhesive with good construction performance, excellent performance, fast curing speed and simple preparation method, so as to better meet the actual application needs of the solar photovoltaic module industry. Summary of the invention

[0006] The purpose of the present invention is to reduce the probability of one-time overflow of the existing sealant and improve the assembly efficiency of the component, ensure the reliability of the component, introduce hydrophobic fumed silica by compounding filler and α, ω-dihydroxy polydimethylsiloxane, and adjust the order of adding auxiliary agents and reaction time, while improving the curing rate of the sealant and adjusting the extrusion property, using modified silicon micropowder to partially replace the active nano calcium carbonate, and adjusting the type, order of adding auxiliary agents and reaction time, to improve the construction performance, curing rate and anti-aging performance of the sealant. Based on this purpose, the present invention provides a photovoltaic module fast-curing anti-aging silicone sealant and a preparation method thereof, comprising the following raw materials in parts by weight: 360-450 parts of α, ω-dihydroxy polydimethylsiloxane, 275-425 parts of nano-active calcium carbonate, 130-280 parts of modified silicon micropowder, 5-10 parts of hydrophobic fumed silica, 30-40 parts of cross-linking agent, 5-10 parts of coupling agent, and 0.1-0.4 parts of dibutyltin dilaurate.

[0007] The α,ω-dihydroxy polydimethylsiloxane comprises 330-375 parts of 10000-20000 mpa.s α,ω-dihydroxy polydimethylsiloxane and 30-75 parts of 400000-700000 mpa.s α,ω-dihydroxy polydimethylsiloxane.

[0008] Preferably, the crosslinking agent is one or a combination of two of methyl tributylacetoximine silane, vinyl tributylacetoximine silane, and D-31 methyl mixed ketoxime crosslinking agent.

[0009] The coupling agent is one or a combination of γ-aminopropyltriethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

[0010] As a further optimization, the viscosity of the α,ω-dihydroxypolydimethylsiloxane at room temperature is 10000-20000 mPa.s and 400000-700000 mPa.s.

[0011] In some preferred cases, the viscosity of the α,ω-dihydroxypolydimethylsiloxane at room temperature is 20,000 mPa.s and 500,000 mPa.s.

[0012] 400000~700000 mpa.s α,ω-dihydroxy polydimethylsiloxane has a longer molecular chain and stronger intermolecular force, which is manifested as a higher viscosity on a macro scale and can be used to adjust the construction performance of the sealant. In addition, long-chain molecules are more likely to entangle with each other during the cross-linking process, forming a more complex and stable three-dimensional network structure. In addition, the hydroxyl content of 400000~700000 mpa.s α,ω-dihydroxy polydimethylsiloxane is lower than that of 10000~20000 mpa.s, which can be used to adjust the hydroxyl value so that each active site is completely cross-linked. Using a higher ratio of 10000~20000 mpa.s and 400000~700000 mpa.s α,ω-dihydroxy polydimethylsiloxane can improve the mechanical properties and construction performance of the sealant, and has a better mechanical property retention rate after aging.

[0013] Preferably, the filler is a mixture of nano calcium carbonate, modified silica powder and fumed silica, and the moisture content of the fumed silica is less than 0.6%. Fumed silica has a good filling effect and can effectively improve the initial mechanical properties of the sealant.

[0014] Preferably, the nano-active calcium carbonate is stearic acid-modified nano-calcium carbonate, and D50 is 2 μm.

[0015] Preferably, the modified silicon powder D50=5-10 m, after 30-35wt% H2O2 is used to activate the silicon micropowder with hydroxyl groups, the chemical vapor deposition method is used, and the siloxane bond directly reacts with the -OH group on the surface of the silicon micropowder under anhydrous conditions to generate a strong Si-O-Si covalent bond, which is grafted on the surface of the silicon micropowder to fully hydrophobically modify it. And under anhydrous conditions, the molecules of the modifier will not condense, and it is easier to modify the monolayer than the liquid phase method. Silicon micropowder is superior to calcium carbonate in terms of chemical stability, thermal stability and enhancement effect. Calcium carbonate has relatively weak weather resistance and is prone to chemical reactions in acidic environments.

[0016] The preparation method of modified silicon micropowder specifically comprises the following steps: Step 1 Take 1000-1250 mesh silicon micropowder and 400 mL 30-35wt% H2O2 and mix them evenly, then stir, condense and reflux at 105℃-115℃ for 3-5 hours to obtain a hydroxyl-activated silicon micropowder solution; Step 2: The powder obtained after filtering the silica powder solution is dried at 100-120°C for 3-4 h and crushed to obtain hydroxyl-activated silica powder with D50=5-10 μm; Step 3 Based on the chemical vapor deposition method, place the hydroxyl activated silicon powder in a tray and a container containing a modifier in a vacuum oven at the same time. The amount of modifier added is 20% of the mass of the silicon powder. 50%, heated to 110~130℃ for 0.5~1 h, carried out vapor deposition process to complete hydrophobic modification, then vacuumed to remove excess gaseous modifier, and cooled to obtain modified silica powder.

[0017] The modifier is one or more of dimethyldiethylsilane, vinyltrimethoxysilane (SCA-1603), vinylmethyldimethoxysilane and aminoethylaminopropylmethyldimethoxysilane.

[0018] The present invention provides a method for preparing a fast-curing anti-aging silicone sealant for photovoltaic modules, which specifically comprises the following steps: Step1 Place α,ω-dihydroxypolydimethylsiloxane, nano-activated calcium carbonate and modified silicon powder in a planetary mill at a speed of 60-80 rpm, mix and heat to 120℃~130℃, vacuum degree -0.095 MPa, and stir at a speed of 80-120 rpm to remove water for 3 h The base material was obtained after 4 h, and the moisture content was less than 0.01%.

[0019] Step2 Add hydrophobic fumed white carbon black to the base material cooled to room temperature, mix at a speed of 60-80 rpm, and then at a vacuum degree of -0.095 MPa, at a speed of 80 Stir at 120 rpm.

[0020] Step3 Add the cross-linking agent to the base material cooled to room temperature and mix evenly, vacuum degree -0.095 MPa, and stir at a speed of 80~120 rpm.

[0021] Step 4: Add coupling agent and catalyst to the base material, vacuum degree -0.095 MPa, stir at 80~120 rpm to obtain fast-curing anti-aging silicone sealant for photovoltaic modules.

[0022] The advantages of the present invention are: (1) 10,000 20000 mpa.s and 400000 The compounding of 700000 mpa.s α,ω-dihydroxy polydimethylsiloxane can significantly improve the elasticity and construction performance of the sealant; (2) Introducing modified silica powder and hydrophobic fumed silica to replace part of nano-calcium carbonate as fillers can improve the mechanical properties of the sealant and make it have better weather resistance; (3) The crosslinker prepared by combining vinyl trisbutyl ketoxime silane and D-31 methyl mixed ketoxime crosslinker has high activity and can effectively improve the curing depth of the sealant and shorten the surface drying time to 5 6 min; (4) The present invention adopts low-cost, safe and non-toxic 30 35wt% H2O2 is used to activate the unmodified silicon micropowder with hydroxyl groups to facilitate full reaction with the modifier and improve the grafting rate. Modification by chemical vapor deposition can timely remove the residual modifier and the modified product, avoid excessive modifier forming multiple layers of physical adsorption on the surface of silicon micropowder, affect the modification effect, and reduce the modification cost. DETAILED DESCRIPTION

[0023] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention so as to provide a more accurate and comprehensive understanding of the present invention, but the present invention is not limited to these embodiments.

[0024] Example 1 7 provides a method for preparing a fast-curing anti-aging silicone sealant for photovoltaic modules, which is described below using Example 1 as an example.

[0025] Example 1 Preparation of Vinyltrimethoxysilane Modified Silica Powder: Step 1 Take 2 g of 1250 mesh unmodified silica powder and 400 mL of 35wt% H2O2 in a three-necked flask and mix them evenly. Then stir, condense and reflux at 110℃ for 4 h to obtain a hydroxyl-activated silica powder solution. Step 2 The powder obtained after filtering the silicon powder solution was dried at 120℃ for 3 h and crushed to obtain D50=10 m hydroxyl activated silica powder; Step 3 Based on the chemical vapor deposition method, the hydroxyl-activated silicon micropowder is placed in a tray and a beaker containing the SCA-1603 modifier is placed in a vacuum oven at the same time. The amount of modifier added is 30% of the mass of the silicon micropowder. It is heated to 130°C for 0.5h to complete the hydrophobic modification, and then the excess gaseous modifier is removed by vacuum. After cooling, the SCA-1603 modified silicon micropowder is obtained.

[0026] Preparation of fast-curing anti-aging silicone sealant for photovoltaic modules Step1: 350 parts of 20000 mpa.s α,ω-dihydroxy polydimethylsiloxane, 50 parts of 500000 mpa.s α,ω-dihydroxy polydimethylsiloxane, 260 parts of nano-activated calcium carbonate and 260 parts of SCA-1603 modified silicon powder were mixed in a planetary mill at a speed of 80 rpm for 30 min, then heated to 130°C, vacuum degree -0.095 MPa, and stirred at a speed of 120 rpm to remove water for 3 hours to obtain a base material with a moisture content of less than 0.01% to ensure the storage period of the sealant; Step 2: Add 10 g of hydrophobic fumed white carbon black to the base material cooled to room temperature, mix at 80 rpm for 15 min, and then stir at 120 rpm for 30 min under a vacuum degree of -0.095 MPa; Step 3 Add 25 parts of vinyl trisbutyl ketoxime silane and 10 parts of D-31 methyl mixed ketoxime crosslinker to the base material cooled to room temperature, and stir at 100 rpm for 15 min under vacuum; Step 4 Add 5 parts of γ-aminopropyltriethoxysilane, 3 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 0.3 parts of dibutyltin dilaurate to the base material, stir at 100 rpm for 15 min under vacuum conditions to obtain a fast-curing anti-aging silicone sealant for photovoltaic modules.

[0027] Example 2 The difference between Example 2 and Example 1 is that the silicon micropowder is not activated with H2O2 for hydroxyl group.

[0028] Example 3 The difference between Example 3 and Example 1 is that silicon micropowder, ie, unmodified silicon micropowder, is used.

[0029] Example 4 The difference between Example 4 and Example 1 is that no nano-activated calcium carbonate is added.

[0030] Example 5 The difference between Example 5 and Example 1 lies in the modification method of the silicon micropowder after the hydroxyl activation is completed.

[0031] The specific modification method is as follows: 20 g of hydroxyl-activated silicon micropowder and 1 g of SCA-1603 modifier are added to a mixed solution of 400 g of ethanol and deionized water in a mass ratio of 1:9, placed in a three-necked flask, and refluxed under high-speed stirring at 80°C in a water bath for 2 h to complete the modification. The modified silicon micropowder is washed with deionized water and ethanol three times respectively, filtered, placed in a vacuum drying oven, dried at 80°C for 4 h, and crushed to obtain D50=10 m's SCA-1603 modified silica powder.

[0032] Example 6 The difference between Example 6 and Example 1 is that 130 parts of SCA-1603 modified silicon powder are added.

[0033] Example 7 The difference between Example 7 and Example 1 is that 50 parts of 500000 mpa.s α,ω-dihydroxypolydimethylsiloxane are not added, and the added amount of 20000 mpa.s α,ω-dihydroxypolydimethylsiloxane is 400 parts.

[0034] Comparative Example 1 Step1: Mix 400 parts of 20000 mpa.s α,ω-dihydroxypolydimethylsiloxane and 520 parts of nano-activated calcium carbonate at 80 rpm for 30 min, then heat to 130°C, vacuum degree -0.095 MPa, and stir at 120 rpm for 3 h to remove water to obtain the base material with a moisture content of less than 0.01% to ensure the storage period of the sealant.

[0035] Step 2: Add 17.5 parts of vinyl trisbutyl ketoxime silane and 17.5 parts of methyl trisbutyl ketoxime silane to the base material cooled to room temperature, and stir at 100 rpm for 15 min under vacuum.

[0036] Step 3: Add 5 parts of γ-aminopropyltriethoxysilane, 3 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 0.2 parts of dibutyltin dilaurate to the base material, and stir at 100 rpm for 15 min under vacuum conditions to obtain a silicone sealant for photovoltaic modules.

[0037] According to Example 1 The photovoltaic module fast-curing anti-aging silicone sealant prepared in Example 7 and Comparative Example 1 was subjected to the following performance tests, and the test results are shown in Table 1.

[0038] Extrusion rate: reflects the construction performance of sealant extrusion, expressed as the time required to extrude 20 g of sealant, the inner diameter of the nozzle extrusion port is 3 mm, and the pressure is 0.5 MPa; Surface drying time: reflects the time it takes for the sealant surface to become non-sticky, in accordance with GB / T 13477.5-2002; Tensile strength: in accordance with GB / T 528-2009; Elongation at break: in accordance with GB / T 528-2009; Shear strength: Anodized aluminum Al-Al, in accordance with GB / T 7124-2008; Curing depth (mm): in accordance with GB / T 29595-2013, test conditions 23℃±2℃ / RH (50±5)%; Heat and humidity aging test: It is a reliability test conducted under harsh conditions with a temperature of 85°C and a humidity of 85%. It is mainly used to test the heat and humidity resistance and overall reliability of the product under harsh conditions of high temperature and high humidity. The aging time is usually 1000 hours (DH1000). Example 1 8 and the sealant of comparative example 1 were prepared into 200 mm 200mm The silicone sheet with a size of 2 mm was subjected to wet heat aging (DH1000) and then subjected to tensile strength test in accordance with GB / T 528-2009, and the retention rate before and after aging was calculated.

[0039] Table 1

[0040] From the data in Table 1, it can be seen that the photovoltaic module fast-curing silicone sealant (Example 1) of the present invention 7) Compared with the sealant using methyl tributylidene silane (Comparative Example 1), it has a faster curing speed, more suitable extrusion performance and higher mechanical property retention rate, which meets the needs of the component factory for improved assembly efficiency and easy construction, reduces the probability of primary and secondary overflow, and ensures the service life and reliability of the component.

[0041] The present invention introduces an appropriate amount of 500000 mpa.s α, ω-dihydroxy polydimethylsiloxane on the basis of the original formula to improve the elasticity and adjust the hydroxyl value. Compared with Example 7, it can be seen that an appropriate amount of 500000 mpa.s α, ω-dihydroxy polydimethylsiloxane effectively improves the elasticity of the colloid.

[0042] From the data of extrudability and tensile strength in Table 1, it can be seen that the present invention can better fill the colloid by adding an appropriate amount of hydrophobic fumed silica, and at the same time optimize the construction performance of sealant extrusion. The compound use of the two coupling agents can effectively improve the adhesion between the sealant and the substrate, and has a higher shear strength.

[0043] The difference in mechanical property retention after the heat and humidity aging test fully demonstrates that the introduction of an appropriate amount of modified silica powder can effectively avoid the attenuation of mechanical properties of silica gel after aging, and has less impact on the initial mechanical properties. The silica powder after hydroxyl activation is more fully modified and has a better anti-aging effect. However, excessive use of silica powder will cause the colloid to become brittle and reduce elongation.

[0044] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A fast-curing anti-aging silicone sealant for photovoltaic modules, characterized in that: The invention comprises the following raw materials in parts by weight: 360-450 parts of α,ω-dihydroxypolydimethylsiloxane, 275-425 parts of nano-activated calcium carbonate, 130-280 parts of modified silicon micropowder, 5-10 parts of hydrophobic fumed silica, 30-40 parts of a crosslinking agent, 5-10 parts of a coupling agent and 0.1-0.4 parts of dibutyltin dilaurate.

2. The fast-curing anti-aging silicone sealant for photovoltaic modules according to claim 1, characterized in that: The α,ω-dihydroxy polydimethylsiloxane comprises 330-375 parts of 10000-20000 mpa.s α,ω-dihydroxy polydimethylsiloxane and 30-75 parts of 400000-700000 mpa.s α,ω-dihydroxy polydimethylsiloxane.

3. The fast-curing anti-aging silicone sealant for photovoltaic modules according to claim 1, characterized in that: The nano active calcium carbonate is nano calcium carbonate modified by stearic acid.

4. The fast-curing anti-aging silicone sealant for photovoltaic modules according to claim 1, characterized in that: The water content of the hydrophobic fumed silica is less than 0.6%.

5. The fast-curing anti-aging silicone sealant for photovoltaic modules according to claim 1, characterized in that: The modified silicon micropowder is modified silicon micropowder obtained by chemical vapor deposition, and the modifier is one or more of dimethyldiethylsilane, vinyltrimethoxysilane, vinylmethyldimethoxysilane and aminoethylaminopropylmethyldimethoxysilane.

6. The photovoltaic module fast-curing anti-aging silicone sealant according to claim 5, characterized in that: Preparation method of modified silicon micropowder, specifically The following steps are involved: Step 1: Mix the silicon micropowder and 30-35wt% H2O2 evenly, and stir, condense and reflux at a temperature of 105℃~115℃ for 3-5 hours to obtain a silicon micropowder solution after hydroxyl activation; Step 2: The powder obtained after filtering the silicon micropowder solution is dried and crushed to obtain hydroxyl-activated silicon micropowder; Step 3 Based on the chemical vapor deposition method, the hydroxyl-activated silicon micropowder and the modifier are placed in a closed container in different areas. The amount of the modifier added is 20%~50% of the mass of the silicon micropowder. The hydrophobic modification is completed by heating to 110~130℃ for 0.5~1 h. The modified silicon micropowder is obtained after vacuuming and cooling.

7. The photovoltaic module fast-curing anti-aging silicone sealant according to claim 1, characterized in that: The crosslinking agent is one or a combination of two of methyl tributylacetoximine silane, vinyl tributylacetoximine silane and D-31 methyl mixed ketoxime crosslinking agent.

8. The photovoltaic module fast-curing anti-aging silicone sealant according to claim 1, characterized in that: The coupling agent is one or a combination of γ-aminopropyltriethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

9. A method for preparing the fast-curing anti-aging silicone sealant for photovoltaic modules according to any one of claims 1 to 8, characterized in that: The specific steps include: Step 1: Mix α,ω-dihydroxy polydimethylsiloxane, nano-activated calcium carbonate and modified silicon powder in a planetary mill, heat to 120℃~130℃ under vacuum, mix and stir to remove water for 3h~4h, and obtain a base material with a moisture content of less than 0.01%; Step2 Add hydrophobic fumed white carbon black to the base material cooled to room temperature, mix well, and stir under vacuum; Step3 Add the crosslinking agent to the base material cooled to room temperature and mix well, stirring under vacuum; Step 4: Add coupling agent and catalyst to the base material, stir under vacuum to obtain fast-curing anti-aging silicone sealant for photovoltaic modules.

Citation Information

Patent Citations

  • Fast cured sealant for solar photovoltaic module and preparation method of sealant

    CN103232832A

  • Substrate non-sticky type silicon rubber sealant and preparation method of substrate non-sticky type silicon rubber sealant

    CN106753200A

  • Solar energy photovoltaic subassembly sealant and preparation method thereof

    CN108048030A

  • Bicomponent silicone structural adhesive for solar thermal power generation and preparation method thereof

    CN109609083A

  • Single-component dealcoholized sealant as well as preparation method and application thereof

    CN116285870A